2021
DOI: 10.1596/1813-9450-9748
|View full text |Cite
|
Sign up to set email alerts
|

Scores, Camera, Action: Social Accountability and Teacher Incentives in Remote Areas

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The impact evaluation of KIAT Guru found that all three treatments improved learning outcomes, with average effect sizes across Indonesian language and mathematics of SD = 0.08 for SAM-only, SD = 0.11 for SAM+Score, and SD = 0.20 for SAM+Cam (see Table 3 in Gaduh et al 2021; see also Gaduh et al 2020). This analysis rejected equality between SAM+Cam and the other two treatment groups (p < 0.02).…”
Section: Kiat Guru Treatment Groups and Outcomesmentioning
confidence: 95%
See 4 more Smart Citations
“…The impact evaluation of KIAT Guru found that all three treatments improved learning outcomes, with average effect sizes across Indonesian language and mathematics of SD = 0.08 for SAM-only, SD = 0.11 for SAM+Score, and SD = 0.20 for SAM+Cam (see Table 3 in Gaduh et al 2021; see also Gaduh et al 2020). This analysis rejected equality between SAM+Cam and the other two treatment groups (p < 0.02).…”
Section: Kiat Guru Treatment Groups and Outcomesmentioning
confidence: 95%
“…This analysis rejected equality between SAM+Cam and the other two treatment groups (p < 0.02). An additional round of data collection for SAM-only and SAM+Cam one year after the endline found that learning outcome gains persisted in SAM+Cam with an effect size of SD = 0.13 on average across the two subjects, whereas learning outcomes in SAM-only were no longer significantly different from the control group (see Table 3 in Gaduh et al 2021; see also Gaduh et al 2020). 7 In addition to the quantitative impact evaluation, a second study drew on three rounds of detailed qualitative fieldwork in nine schools, with three schools from each of the three treatment groups.…”
Section: Kiat Guru Treatment Groups and Outcomesmentioning
confidence: 98%
See 3 more Smart Citations